2016
DOI: 10.1111/hae.12894
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a high‐purity plasma‐derived factor X concentrate in subjects with moderate or severe hereditary factor X deficiency

Abstract: This is the most comprehensive PK study to date in subjects with hereditary FX deficiency. These results are consistent with the observed haemostatic efficacy of pdFX and provide the PK data required for the treatment of hereditary FX deficiency using pdFX replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 23 publications
0
29
0
1
Order By: Relevance
“…Several studies have been published on the use of pdFX in subjects ≥12 years old with hereditary FXD . However, data describing the use of FX‐specific treatments in children <12 years old are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been published on the use of pdFX in subjects ≥12 years old with hereditary FXD . However, data describing the use of FX‐specific treatments in children <12 years old are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma‐derived factor X (pdFX) is a novel, high‐purity, high‐potency FX concentrate approved in the United States for on‐demand treatment of hereditary FXD in adults and children (aged 12 years and above) and in the European Union for the prophylactic and/or on‐demand treatment of hereditary FXD (marketed under the commercial name Coagadex ® [Bio Products Laboratory, Elstree, UK]) . The safety and efficacy of pdFX as short‐term prophylactic and on‐demand treatment for subjects ≥12 years old with moderate and severe FXD has been established, but data in children <12 years are limited to 3 children who received pdFX on a compassionate use basis. This study was therefore conducted to investigate the efficacy, safety and pharmacokinetics of pdFX in the prophylactic and on‐demand treatment of moderate or severe hereditary FXD in children <12 years.…”
Section: Introductionmentioning
confidence: 99%
“…With a clinical half‐life of 29.4 hours, pdFX has potential for once‐ or twice‐weekly prophylactic administration. However, maintaining adequate hemostasis during surgery is challenging for rare hereditary bleeding disorders; particularly in acute bleeding with coagulation factor consumption and loss, shorter dosing intervals might be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent pharmacokinetic analysis confirmed that replacing FX every 18 hours was necessary to maintain trough levels of FX above 50%, leading to clinical rehabilitation with no neurologic deficits. This therapeutic regime was guided by the results of plasma‐based coagulation assays, as in vitro nonclinical coagulation tests (prothrombin time, aPTT, and thrombin‐generation assay) have demonstrated that pdFX corrects plasma FXD in a dose‐dependent manner …”
Section: Discussionmentioning
confidence: 99%
“…The thrombotic risk associated with PCCs and rFVIIa may be eliminated by the use of a high‐purity plasma derived factor X concentrate, developed by BPL (Bio Products Laboratory Ltd., Elstree, UK), which is currently under priority review by the US Food and Drug Administration (FDA). In patients with hereditary factor X deficiency, BPL factor X has a half‐life of approximately 30 h with a factor X incremental recovery of about 2 IU/dL per IU/kg . Although BPL factor X was not evaluated in clinical trials in patients with acquired factor X deficiency, Mahmood et al .…”
Section: Discussionmentioning
confidence: 99%